Technology-Based Competency Improvement Through Digital Marketing Training at The Job Training Institute (LPK) Bina Mandiri Center-Bandung City - Rini Handayani; Andhi Sukma; Fansuri Munawar; Aditya Yudanegara; Irma Nilasari; Ayuningtyas Y. Hapsari; Desy Oktaviani (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Marketing trends have shifted from conventional (offline) to digital (online). With digital marketing, it can reach all people wherever they are without any geographical and time restrictions. Business actors have started using digital marketing as a promotional tool, but not optimally, because they are hindered by the constraints of still needing to gain knowledge about digital marketing. Therefore, it is necessary to socialize and train the use of information and communication technology so that it is expected to provide knowledge and understanding and inspire business actors to utilize technology as a tool to run their business. This PKM program will target LPK Bina Mandiri Center partners on Jl. Tubagus Ismail No. 57, Sekeloa Village, Coblong District, Bandung City. This program will focus on improving the knowledge and skills of business actors through digital marketing training according to partners' needs.